Seroepidemiological study reveals regional co‐occurrence of Lassa‐ and Hantavirus antibodies in Upper Guinea, West Africa. Issue 3 (31st December 2012) - Klempa, Boris; Koulemou, Kekoura; Auste, Brita; Emmerich, Petra; Thomé‐Bolduan, Corinna; Günther, Stephan; Koivogui, Lamine; Krüger, Detlev H.; Fichet‐Calvet, Elisabeth
Abstract Objectives To assess the public health relevance of Lassa arenavirus and hantavirus infections in a subpopulation of recently febrile patients. Methods In a human seroprevalence study, we enrolled 253 participants on the basis of reported high fever during the last 3 months. They represented roughly 20% of the population of Bantou and Tanganya villages. Comprehensive serological screening and confirmatory assays (enzyme‐linked immunosorbent assay, immunofluorescence assay, Western blot analysis) with several Lassa virus and hantavirus antigens were used to ensure high specificity and broad detection capacity. Results We found a Lassa IgG prevalence of 40.3% (102/253) and a hantavirus IgG prevalence of 1.2% (3/253). The Lassa IgM prevalence reached 2.8% (7/253). Conclusions High Lassa virus seroprevalence in recently febrile patients indicates that Lassa fever is a significant public health problem in the region. Human hantavirus infections also occur in the region but their public health relevance remains to be determined.